Impact of system parameters on the penetration of lightning surges into low voltage systems - Shareef, H. (IEEE Explorer, 2011)
Power system disturbances have been present since the inception of the electric utility industry. However, yesterday's loads are more forgiving of disturbances than today's modern equipment. The proliferation of sensitive electronic equipments such as PCs, variable speed drives and industrial programmable controllers has made us more aware of power system disturbances, which went unnoticed in the past. In the normal operation of power systems, unavoidable disturbances may happen due to switching actions, faults and lightning overvoltage surges. Overvoltage surges are damaging in nature and result in more frustrations and even fire in rare cases. This research aims to investigate the impact of overvoltage surges due to various types of lightning on a low voltage system. It is done through simulation conducted under various scenarios. Then based on the simulation results and parametric evaluation, the impacts of different system parameters are finally summarized.